Percutaneous Nephrolithotomy: A Comparison of Tubeless versus the Standard technique - Zein El Amir; Muhammad Ali Shahiman; Zeeshan Qadeer; Rameez Ahmed Mughal; Ashfaq Ali (Journal of Rawalpindi Medical College, 2021)
Objective: The proposed study aimed to assess the utility of tubeless PCNL in terms of efficacy and safety when compared with the standard tubed PCNL.